Local side effects during sublingual allergen-specific immunotherapy and pathogenetically based methods for their correction (Review) - V. Ya. Zakurskaya (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Introduction. The study of the effectiveness and safety of allergen-specific immunotherapy remains relevant due to the emergence of a personalized approach in allergology and new dosage forms. Adverse reactions during sublingual allergen-specific immunotherapy are the leading reason of treatment discontinuation. Understanding the mechanisms of side effects and knowing how to overcome them allows us to achieve better tolerability of allergen-specific immunotherapy and maintain patient compliance.The aim of the review is to combine the available literature data on the frequency, nature, and pathogenetic basis of adverse events during sublingual allergen-specific immunotherapy and to consider options for their prevention and treatment.